Monitoring trends in illicit drug use in Europe: an overview of the work of the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) - Griffiths, Paul; Lopez, Dominique; Götz, Wolfgang (Psychiatrie und Psychotherapie, 2008)
Summary For more than 10 years, the EMCDDA has been working to develop a drug monitoring system for Europe. Here, we describe the approach taken to collect and report on data-use issues, placing it within the general context of developments in European integration. The extent to which the European data collection system has developed is explored by presenting an overview of what they reveal about current trends in illicit drug use in Europe. METHODOLOGICAL APPROACH: The EMCDDA is a decentralised technical agency of the European Union. The role of the Centre is to provide sound and reliable information on drugs. Reporting covers: the epidemiological situation; responses; and drug strategies and policies. The Centre works closely with national focal points located in all participating countries to develop standard and comparable measures, methods and reporting tools. Among the most established of these are the five key epidemiological indicators. DISCUSSION: Data availability has increased considerably in Europe since the mid-1990s and now permits a general overview of trends to be made informed by an understanding of both the strengths and weaknesses in the information base. This provides information useful for evaluating actions at a European level and also facilitates a debate among Member States by providing a 'common language' for describing their drug situation. The reporting system has also acted as a catalyst for national data collection activities and methodological developments.